Integrated 256 cell photonic phase-change memory with 512-bit capacity - Feldmann, J; Youngblood, N; Li, X; Wright, CD; Bhaskaran, H; Pernice, WHP (Institute of Electrical and Electronics Engineers, 2019)
All-optical nonvolatile memories enable storage of telecommunication data without detours through electronic circuitry. Phase-change materials provide the means to embed such memories within integrated optical circuits and thus allow combining waveguide devices for information processing with local data storage. Using this concept, we realize an all-photonic memory circuit capable of storing 512 bits of data in an array of nanoscale phase-change devices. We employ multilevel addressing and wavelength multiplexing of microring resonators to write and read a 16 × 16 greyscale image with 2-bit resolution entirely in the optical domain. Our approach holds promise for implementing scalable architectures for on-chip optical data storage with long data retention and ultrafast access times.